La poesia in lingua italiana di Francisco de Quevedo - VENTURA , Edoardo (Cuadernos de Filología Italiana, 2010)
In European heteroglossia, the Italian compositions of Francisco de Quevedo play an absolutely important role for the description of the event. This paper deals with the analysis of the Spanish poet’s Italian works – two sonnets, either belonging to political themes, either one to love poetry – relating to his own literary production in Spanish and to the Petrarchan and Italian tradition. Different levels of intertextuality that offer a preferential view of this anomalous artistic process, searching for the deep reasons behind a great’s poet choice to write in another language.